Embedded LoRaWAN for agricultural sensing applications - Suwaid, Maged Mohammed; Habaebi, Mohamed Hadi; Khan, Sheroz (IEEE, 2020)
Recently, the concept of the wireless sensor network in agriculture spread around the world to help farmers to enhance the productivity and quality by continuously monitoring the crops development. In contrast, the environment of farms does not assist the implementation of IoT because of the difficulty to find the power supply. Sometimes, farmers face some difficulty to track their plants because of types of the environment. For example, the desert and high temperature, and the tropical forest and rainy seasons incur harsh operating scenarios. Therefore, this work aims to create a system that helps farmers to track their crops remotely using LoRaWAN technology. The features of the system are very low power consumption and large coverage area of the signal which are the most important features suitable for farming environment. The sensors help give a very important information to farmers too. The work began with selecting the appropriate, cost-effective sensors to be deployed. Then, a design or integration was proposed for the system and the associated peripherals. The system will comprise of a LoRa node, is responsible for collecting data from the sensors, and a LoRa Gateway, that is accountable for receiving the data, to send it to The Things Network (TTN) server. So, the Arduino code will be used to program the sensor to collect data and send it to the gateway to be displayed on TTN. In addition, with the help of integration between the TTN and the Ubidots, the data can be easily analyzed and monitored from the website and the app of Ubidots. Later, the field test implemented on plant for almost one week, to demonstrated the ability of the proposed system to work.